2018
DOI: 10.1111/1440-1630.12491
|View full text |Cite
|
Sign up to set email alerts
|

The impact of carer status on participation in healthy activity and self‐reported health among Australian women over 50 years

Abstract: These findings indicate significant differences between women with and without caregiving responsibilities and their participation in health promoting activities, self-reported mental health, participation in physical activity and the labour force. Carers may benefit from occupational therapy that recognises the important role of carers in the life of their family member and supports carer's health and participation in health promoting activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The other pathway that leads to chronic stress may promote carer's unhealthy behaviours such as, drug and alcohol abuse, smoking, poor nutrition, and sedentary lifestyle, that are often associated with physical and mental health problems [20]. In an Australian study of women aged 50 years or more, carers reported higher symptoms of depression, anxiety and stress than non-carers [26]. This study also, reported significantly lower participation in health promoting activities and physical activities [26].…”
Section: Carer Health Behaviour and Healthmentioning
confidence: 71%
See 2 more Smart Citations
“…The other pathway that leads to chronic stress may promote carer's unhealthy behaviours such as, drug and alcohol abuse, smoking, poor nutrition, and sedentary lifestyle, that are often associated with physical and mental health problems [20]. In an Australian study of women aged 50 years or more, carers reported higher symptoms of depression, anxiety and stress than non-carers [26]. This study also, reported significantly lower participation in health promoting activities and physical activities [26].…”
Section: Carer Health Behaviour and Healthmentioning
confidence: 71%
“…In an Australian study of women aged 50 years or more, carers reported higher symptoms of depression, anxiety and stress than non-carers [26]. This study also, reported significantly lower participation in health promoting activities and physical activities [26]. Consequently, there is a need to understand the link between caregiving, carer's healthy behaviour and health.…”
Section: Carer Health Behaviour and Healthmentioning
confidence: 75%
See 1 more Smart Citation
“…Therefore, high intensity caregiving suits well neither with full-time workforce participation nor with non-workforce participation in influencing physical and mental health of carers. Farrugia et al (2018) found as well that in Australia, women carers reported worse mental health than non-carers while they were also, more likely to be working part-time or not be working at all 25 . Thus, there is a clear need for understanding the potentially modifying or protective effects of workforce participation on carer health, which is one of the focuses of this study.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 93%
“…The other pathway that leads to chronic stress may promote carer's unhealthy behaviours such as, drug and alcohol abuse, smoking, poor nutrition, and sedentary lifestyle, that are often associated with physical and mental health problems 19 . In an Australian study of women, aged 50 years or more, carers reported higher symptoms of depression, anxiety and stress than non-carers 25 . They also, reported significantly lower participation in health promoting activities and physical activities 25 .…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 93%